Simplified digital infra red photography: an alternative tool in Bite mark forensic investigation - Haryono Utomo; Mieke Sylvia (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: Decades ago, documentation of forensics evidences such as bitemarks, bloodstains and others which required sophisticated photographic techniques and equipments such as infrared (IR) and ultraviolet (UV) photography, became a problem since they only use film that must be developed. Therefore, direct evaluation of the photographic result could not be directly visualized. The equipments prices were relatively high. Moreover, most of the equipments were still not available and relatively expensive; and converted IR digital camera could not use for regular photography. Recently, digital camera made image documentation and editing easier. Purpose: This review was aimed to explore the different characteristics and benefits of regular digital camera in IR forensic photography as well as to simplify the equipments needed. Reviews: IR photography becomes easier since certain digital cameras could capture the IR image by using IR filters or to be switched to IR camera. The regular non-SLR digital camera had certain advantages compared to SLRs, such in focusing. However, since not every digital camera has the ability to capture IR light, laser pointer or TV remote could be used as a tester. Conclusion: Knowledge about IR Bite mark photography, characteristics of regular digital camera and its accesories could reduce the budget for an ideal standard forensic photographic equipments by modifications.Latar belakang: Puluhan tahun silam, dokumentasi bukti forensik seperti teraan gigit, bercak darah dan sebagainya yang memerlukan teknik dan peralatan yang canggih seperti fotografi infra merah (IR) dan ultraviolet (UV) merupakan masalah karena memakai film yang harus diproses terlebih dahulu untuk mengetahui hasilnya. Akibatnya, hasil pemotretan tidak bisa langsung dievaluasi, selain itu harganya relatif mahal, kamera digital yang diubah menjadi kamera IR tidak bisa untuk pemotretan biasa. Saat ini kamera digital dan program komputer mempermudah dokumentasi dan penyuntingan. Tujuan: Tujuan dari tulisan ini adalah untuk menjabarkan sifat dan keuntungan kamera digital dalam fotografi IR forensik dan menyederhanakan peralatan yang dibutuhkan. Tinjauan pustaka: Fotografi IR dipermudah karena kamera digital tertentu dapat menangkap gambar IR dengan menggunakan filter IR atau diubah menjadi kamera digital IR. Kamera biasa non-SLR mempunyai beberapa keuntungan dibandingkan SLR antara lain dalam memfokuskan obyek. Walaupun demikian, karena tidak semua kamera digital biasa dapat menangkap sinar IR, dapat dilakukan pengujian dengan penunjuk laser atau pengatur jarak jauh televisi. Kesimpulan: Pengetahuan tentang fotografi IR, kamera digital biasa dan peralatan tambahannya dapat mengurangi biaya peralatan fotografi IR standar forensik dengan cara modifikasi.